PHYSICOCHEMICAL PARAMETERS IN ESTUARINE ZONES OF THE TODOS OS SANTOS BAY IN BAHIA, BRAZIL - Milazzo, Alexandre Dacorso Daltro; Cruz, Manoel Jerônimo Moreira; de Melo, Eduardo Gomes Vieira (Geochimica Brasiliensis, 2017)
The physicochemical parameters in both surface waters and sediments are important to understand estuarine dynamics. Different input of natural process along the year like rainfall, land breezes, solar radiation and fresh water influx as well as different location will change the physicochemical parameters. The present study was carried out to determine how the spatial-temporal difference will affect physicochemical parameters at three different locations from the Todos os Santos Bay. This involved analyzing pH, Eh (mV), temperature (ºC), salinity (‰), dissolved oxygen (mg L-1) and conductivity (ms cm-1) in the water and pH, Eh (mV), Temp. (ºC) and conductivity (ms cm-1) in the sediments. Particle size and organic matter also was analyzed in the sediments. The results showed that the values of the all parameters were different according the sampling time as well as the location in the bay. The temperature of the surface water, for example, was higher during the dry season (1st and 3rd sampling time) as well as the salinity. The pH of the surface water was higher in the Maragojipe River (7.70) and in the sediment São Paulo River showed the highest result (7.23). The organic matter in the sediment showed the lower percentage during the rainy season (2nd sampling time) and this parameter is strongly associated with the particle size. These results suggests that spatial variation along the bay together with the seasonality affect all the physicochemical parameters in the estuary.